2018
DOI: 10.1093/ofid/ofy133
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and Leprosy Coinfection: A Perspective on Diagnosis and Treatment

Abstract: Both leprosy and tuberculosis (TB) are known to have similar geographic endemicity. In the setting of coinfection, interferon-gamma release assays (IGRAs) to detect latent TB can be falsely positive. We report a case of leprosy with a positive IGRA and asymptomatic active pulmonary TB. Minocycline and dapsone therapy was initiated during the workup for TB and changed to rifampin (Rif), isoniazid, pyrazinamide, and ethambutol, with the addition of dapsone once coinfection was confirmed. Our review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…32 This observation supported a potential function of rs17855750 and might partially explain the low frequent co-infection of leprosy and tuberculosis in clinical practice. [33][34][35][36] We also found an experiment-wide (p < 3.38 × 10 −3 ) significant hit rs45507693 (p.A106T) of IL1RN and a marginally significant (p = 3.45 × 10 −3 ) variant rs3917322 in 3'-UTR of IL1R1 that increase leprosy risk, indicating a potentially active role of the IL1-mediated signaling pathway in leprosy. This finding has not been highlighted in previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…32 This observation supported a potential function of rs17855750 and might partially explain the low frequent co-infection of leprosy and tuberculosis in clinical practice. [33][34][35][36] We also found an experiment-wide (p < 3.38 × 10 −3 ) significant hit rs45507693 (p.A106T) of IL1RN and a marginally significant (p = 3.45 × 10 −3 ) variant rs3917322 in 3'-UTR of IL1R1 that increase leprosy risk, indicating a potentially active role of the IL1-mediated signaling pathway in leprosy. This finding has not been highlighted in previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…Leprosy, a disease caused by M. leprae has similar geographic endemicity as TB. A total of 14 adult co-infected cases have been published to date (180). There is no clear consensus on whether prior exposure to one mycobacteria offers protection or predisposition to the other, but several authors have suggested that impaired cell mediated immunity in patients with multibacillary leprosy may predispose them to TB co-infection (181, 182).…”
Section: Leprosymentioning
confidence: 99%
“…The selected articles -according to the established eligibility criteria -, and analyzed, after completing the review phases, are presented in Tables 1 and 2. All were case report studies; one of the articles was a case series, in a total of 18 patients [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%